Corre um rio de lembranças nas encantadas lavadeiras de Almenara: cotidiano, memória e oralidade nos cantos de trabalho - Jéssica Parreiras Marroques (2022)
Memories build patchwork. What matters to it is the work of stitching, in the mending of a wide river of affections, that builds us. Where I was born, a river flows by. Where most of us were born, grew up, and live, a river still flows by. They roam the ground, they walk under the earth and the concrete, they fly over us in clouds, whispering in resistance the materiality of diverse crafts, practices, rites, and enchantments that submerge and inhabit it. Its waters reveal the lives and stories of the washerwomen, who keep in the weaving of their narratives the wisdom of the songs, the smells, the nature, the fabrics, and the techniques in their daily lives. In this way, this essay research is sewn around the singing in work context, in choir, collective, as expression and cultural experience by the women who compose the Washerwomen Choir of Almenara, in the region of Vale do Jequitinhonha/MG. Here, I propose the interweaving and reflection of the act of singing, washing clothes and collective work, practices that correlate with the universe of work and leisure, of joy, dreams, play, achievements and personal accomplishments of these women, in a thread of memory that connects the practice of singing to the waters and the work of a washerwoman. This work takes us back to the dialogue between past and present in the history of slavery of black diasporic women to the daily act of reproduction and maintenance of life through domestic work.